Legal Protection for Minority Shareholders in Limited Liability Companies According to the PT Law - Polontoh, Herry; Fadhilah, Nurul; Tuhumury, Harry A; Sembiring, Tamaulina Br (PT. Anagata Sembagi Education, 2025)
Minority shareholders play an important role in the ownership structure of Limited Liability Companies (PT), but often face challenges due to the dominance of majority shareholders. This power imbalance threatens minority rights such as access to information, dividend distribution, and voting rights in General Meetings of Shareholders (GMS). Law No. 40/2007 on Limited Liability Companies (PT Law) provides legal protection for minority shareholders, but its implementation still faces obstacles such as weak supervision, lack of legal understanding, and regulatory gaps. This research uses a normative juridical method to analyze legal protection for minority shareholders, including a review of legal norms, doctrines, and court decisions. The results show that although the Company Law has provided a legal foundation, there are still gaps between ideal norms and business practices, such as manipulation of GMS results by the majority or limited transparency. Regulatory reform is needed to strengthen supervision, increase sanctions, and adopt international best practices, such as appraisal rights in the United States. These measures are expected to create more inclusive, fair and sustainable corporate governance, while increasing investor confidence in Indonesia's capital market.